PEMANFAATAN MEDIA PEMBELAJARAN GEOGRAFI BERBASIS MEDIA SOSIAL INSTAGRAM TERHADAP AKTIVITAS SISWA - Noura Rizqyannisa Hidayat (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2024)
This literature review aims to find out about the use of geography learning media based on the social media Instagram on student activities. Geography learning will be more effective if it uses teaching aids or is shown on media. This is in accordance with the opinion of several experts that learning outcomes will be much better if learning media are used appropriately and well. Geography learning media based on the social media Instagram should provide interesting pictures and videos as well as short explanations so that they are easier for students to understand. Teachers who will use Instagram social media-based learning media in learning must learn how to design the images and videos that will be used so that the learning media used during the teaching and learning process is digital-based. It is hoped that the results of this research can contribute to schools to enrich creative, innovative learning media and keep up with technological developments so that they can increase student motivation and learning outcomes.